1978
DOI: 10.1111/j.1399-3054.1978.tb01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Aspects of Senescence in Detached Tobacco Leaves

Abstract: The objective of the present work was to describe the simultaneous changes in endogenous levels of cytokinins, abscisic acid, indoleacetic acid and ethylene in detached, senescing tobacco (Nicotiana rustica L.) leaves. These measurements were related to changes in chlorophyll contents, '^COj fixation and proline contents -three parameters which have been considered to reflect senescence. Effects of exogenous hormonal treatments on these parameters, as well as on endogenous hormonal levels, provided further evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…As leaves begin to senesce, the cytokinin level in xylem sap (Sitton, Itai & Kende, 1967;Hewett & Wareing, 1973 ;Nooden, Singh & Letham, 1990) and leaves (Singh, Letham & Palni, 19926) declines markedly. Even-Chen, Atsmon & Itai (1978) detected a decrease in the endogenous cytokinin level of detached leaves before any major changes in the measured parameters of senescence were detected. This suggested that the drop in the cytokinin level could be related to the induction of senescence in detached leaves.…”
Section: Plant Grozcth Regulators (A) Cytokininsmentioning
confidence: 99%
“…As leaves begin to senesce, the cytokinin level in xylem sap (Sitton, Itai & Kende, 1967;Hewett & Wareing, 1973 ;Nooden, Singh & Letham, 1990) and leaves (Singh, Letham & Palni, 19926) declines markedly. Even-Chen, Atsmon & Itai (1978) detected a decrease in the endogenous cytokinin level of detached leaves before any major changes in the measured parameters of senescence were detected. This suggested that the drop in the cytokinin level could be related to the induction of senescence in detached leaves.…”
Section: Plant Grozcth Regulators (A) Cytokininsmentioning
confidence: 99%
“…In some plant tissues, auxins stimulate ethylene synthesis (Even-Chen et al, 1978;Van Der Straeten et al, 1990) and ethylene synthesis can be induced by auxins in a tissue-specific manner (Van Der Straeten et al, 1990;Yip et al, 1992). Both Ethrel and IAA can induce stomatal opening in epidermis detached from leaves of Vicia faba (Levitt et al, 1987), and there is evidence that auxin-induced stomata1 opening (Levitt et al, 1987;Marten et al, 2991) is mediated through auxin-induced ethylene synthesis (Levitt et al, 1987 ethylene synthesis is required both for growth of callus and for embryo maturation (Kepczynski et al, 1992).…”
Section: Electrophoresis Of Total Sds-extractable Proteinsmentioning
confidence: 99%
“…Additionally, an increase in free IAA level was found in the course of leaf senescence so far in tobacco (13), oat (23), and bean (24) leaves. In the last system, the increase in free IAA level was accompanied by a decrease in the level of IAA conjugates (24).…”
mentioning
confidence: 99%